Financial Performance Analysis Before and After Covid-19. Study of a Case in PT. ANTAM Tbk - Anggun Permata Husda; Hermaya Ompusunggu; Haposan Banjarnahor (eCo-Buss, 2023)
Analysis of PT ANTAM Tbk's Financial Performance Before and After Covid-19 is the title of this study. By comparing the financial ratios of the current ratio, quick ratio, debt to total assets, debt to total equity, net profit margin, return on assets, and total asset turnover, this study seeks to determine the financial ratios of PT ANTAM Tbk before and after COVID-19. The descriptive research method with a comparative study approach was used in this study. The financial statements of PT ANTAM Tbk before and after COVID-19 make up the study's population. Due to the sampling strategy, whereas the sample was taken using the purposive sampling method . The results of the study indicate that the present ratio will be around 144.81% in 2019. The quick ratio is around 1%. Debt to equity is 0.66%, debt to total assets is 0.40%. Return on assets is 6.4%. The net profit margin was 5.92%, while the overall asset turnover was 108%. The current ratio was approximately 121.14% in 2020. The quick ratio is around 1.23%. Debt to total equity is 0.66%. Debt to total assets is 40%. Return on assets was 0.036%. Net profit margin was 0.04%. Total asset turnover is 0.86%.